Structural environmental enrichment improves Nile tilapia flesh quality - Neto, João Favero [UNESP]; Lala, Bruno [UNESP]; Santos, Carolina [UNESP]; Roça, Roberto de Oliveira [UNESP]; de Oliveira, Rogério [UNESP]; Maia, Caroline Marques [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (My University, 2024)
Environmental enrichment is a reliable and useful tool for improving fish welfare in farms. Structural enrichment is widely studied and applied to fish, with positive effects also on the zootechnical parameters of fish farming. In our study, we examined whether artificial shelters and water hyacinth-structural enrichments-improve the quality of tilapia fillets. Tilapia juveniles (n = 480) underwent three independent treatments over 100 days: artificial water hyacinth enrichment, shelter enrichment, and control (no enrichment). After slaughtering, we evaluated physical-chemical indicators of meat quality. Whereas meat pH was not affected by the availability of enrichment, we found less lightness in terms of chroma b* of the flesh from tilapia raised with artificial water hyacinth and more flesh toughness in the texture of tilapia raised with shelter, indicating a higher-quality product. Regarding the fatty acid profile, differences were found when individually analyzed. All fatty acids that differed among treatments (C4:0, C23:0, C24:0, C16:1, and C24:1) exhibited better performance in groups reared with structural enrichment. In conclusion, improving Nile tilapia welfare with structural enrichment enhances its flesh quality. Thus, in addition to promoting the welfare of farmed fish, this enrichment may benefit both farmers and consumers.
Keywords: Aquaculture; Fish farming; Fish fillet; Fish welfare, Meat quality, Oreochromis niloticu